THE USE OF THINK-PAIR-SHARE (TPS) STRATEGY TO ENHANCE SPEAKING SKILL OF THE STUDENTS OF THE PESANTREN DDI BARUGA, MAJENE - Muhammad Ardan; Ahmad Talib; Fitri Radhiyani (International Journal of Business English and Communication, 2024)
The purpose of the research is to find out the “Think-Pair-Share Strategy” to enhance speaking skill of the students of the Pesantren DDI Baruga, Majene. This research used pre-experimental design with one-group pretest-posttest. The population in this research is the second-year students of Pesantren DDI Baruga in academic year 2023/2024. This research used purposive sampling technique which the sample of the research was Class XI IPA at Pesantren DDI Baruga, which has 30 students. The findings of this research that there is a significant improve in students speaking skill after the students were given treatments. It can be seen by the mean score between the pre-test (60.70) and the post-test (68.76). Based on students’ mean score, it shows that the Think-Pair-Share as a strategy was able to improve students’ speaking skill. This strategy can demand and force the students to be actively in the learning process especially in speaking skill. Besides, this strategy also can be used as an alternative or guide for teacher to attract student enthusiasm in learning process.